-5(6y-3)-y=-3(y-2)

Simple and best practice solution for -5(6y-3)-y=-3(y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(6y-3)-y=-3(y-2) equation:


Simplifying
-5(6y + -3) + -1y = -3(y + -2)

Reorder the terms:
-5(-3 + 6y) + -1y = -3(y + -2)
(-3 * -5 + 6y * -5) + -1y = -3(y + -2)
(15 + -30y) + -1y = -3(y + -2)

Combine like terms: -30y + -1y = -31y
15 + -31y = -3(y + -2)

Reorder the terms:
15 + -31y = -3(-2 + y)
15 + -31y = (-2 * -3 + y * -3)
15 + -31y = (6 + -3y)

Solving
15 + -31y = 6 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
15 + -31y + 3y = 6 + -3y + 3y

Combine like terms: -31y + 3y = -28y
15 + -28y = 6 + -3y + 3y

Combine like terms: -3y + 3y = 0
15 + -28y = 6 + 0
15 + -28y = 6

Add '-15' to each side of the equation.
15 + -15 + -28y = 6 + -15

Combine like terms: 15 + -15 = 0
0 + -28y = 6 + -15
-28y = 6 + -15

Combine like terms: 6 + -15 = -9
-28y = -9

Divide each side by '-28'.
y = 0.3214285714

Simplifying
y = 0.3214285714

See similar equations:

| 3x+2/x=7 | | -2/5m=4 | | 9/4r=-27/32 | | 102-2x=34x+18 | | 27x-7=16x-18 | | 5x+4x=8x-2 | | -1/6x=-5 | | 63pqrs+45q*2rs-27qrs= | | x+4*(x+4)-10=48 | | 1/8a=1/3 | | x+4times(x+4)-10=48 | | x^2+18x+14=7x+4 | | 6(9x-4)-3(7x-8)=0 | | x+4x(x+4)-10=48 | | 3/4w=21/30 | | 12-10x=25-7x | | a(a-1)=2 | | 2(x-4)-4(x-2)=x+9-(x-3) | | 8(x+3)=5x | | 2/3d=14/15 | | 3x/4-1/5+2x=5/4-3x/20 | | 7x+20=26 | | 5/6n=15 | | 2(x+4)/6=3x-5 | | 14p+14=126 | | 1/2(10z+8)-2=4(z-8) | | p-14=-25 | | 2/n+6/8 | | s-20=-3 | | 25x+100=300 | | (x-2)/(x+6)=2/6 | | 550.00x+175000.00=1680.00+35000.00 |

Equations solver categories